2012
DOI: 10.1177/0954405412447484
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the cutting performance of nano-crystalline diamond coatings on a micro-end mill

Abstract: In conventional milling, appropriate coatings can be used on tools to enhance their cutting performance and efficiency of the production process. In an effort to improve the tooling performance in micro-scale milling, nano-crystalline diamond films were applied on a micro-end mill by a hot filament chemical vapour deposition process. The cutting performance of the nano-crystalline diamond-coated tool, including cutting forces, tool integrity, surface roughness and burr formation, were evaluated in slot milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…16 The aluminium alloy is most commonly used in the fundamental research of ultraprecision and diamond turning especially in evaluation and validation of the material constitutive model, micro cutting characteristics, the process optimization, and so on. [17][18][19] In this article, an innovative cutting force modelling approach is proposed for ultraprecision and micro cutting based on the specific cutting force at the unit length or area and the cutting force analysis against a short dynamic interval of cutting time. The specific cutting force at the unit length or area is called the amplitude aspect of the model formulation, while the force analysis against a short cutting time interval is called the spatial aspect of the formulation.…”
Section: Introductionmentioning
confidence: 99%
“…16 The aluminium alloy is most commonly used in the fundamental research of ultraprecision and diamond turning especially in evaluation and validation of the material constitutive model, micro cutting characteristics, the process optimization, and so on. [17][18][19] In this article, an innovative cutting force modelling approach is proposed for ultraprecision and micro cutting based on the specific cutting force at the unit length or area and the cutting force analysis against a short dynamic interval of cutting time. The specific cutting force at the unit length or area is called the amplitude aspect of the model formulation, while the force analysis against a short cutting time interval is called the spatial aspect of the formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Tool coatings such as diamondlike carbon and nanocrystalline carbon have been shown to prolong the onset of BUEs in microscale tools [8]. However, the lifetime of these coatings is highly unreliable, thereby limiting the potential of this approach [9]. The use of cutting fluids during micromilling reduces the formation of BUEs in metals [5,10], However, cutting fluids are not suited for soft materials such as thermoplastic polymers that are notorious for forming BUEs during micromilling [11].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical vapor deposition (CVD) diamond-coated tool has the most extreme properties such as excellent tribological properties and superior wear resistance, which has been applied for machining Al 2 O 3 ceramics material, carbon fiber-reinforced plastics (CFRP), Al alloy and monocrystalline silicon. [5][6][7][8][9] The CVD diamond-coated tool also has distinct advantage over other coated tool during machining graphite. It is found that the tool life of the diamond-coated driller was six times of the TiAlN-coated one when microdrilling of the graphite.…”
Section: Introductionmentioning
confidence: 99%